Heterozygous Deep-Intronic Variants and Deletions in ABCA4 in Persons with Retinal Dystrophies and One Exonic ABCA4 Variant - Bax, Nathalie M.; Sangermano, Riccardo; Roosing, Susanne; Thiadens, Alberta A.H.J.; Hoefsloot, Lies H.; van den Born, L. Ingeborgh; Phan, Milan; Klevering, B. Jeroen; Westeneng-van Haaften, Carla; Braun, Terry A.; Zonneveld-Vrieling, Marijke N.; de Wijs, Ilse; et al. (Human mutation, 2015)
ABSTRACT Variants in ABCA4 are responsible for autosomal‐recessive Stargardt disease and cone‐rod dystrophy. Sequence analysis of ABCA4 exons previously revealed one causative variant in each of 45 probands. To identify the “missing” variants in these cases, we performed multiplex ligation‐dependent probe amplification‐based deletion scanning of ABCA4. In addition, we sequenced the promoter region, fragments containing five deep‐intronic splice variants, and 15 deep‐intronic regions containing weak splice sites. Heterozygous deletions spanning ABCA4 exon 5 or exons 20–22 were found in two probands, heterozygous deep‐intronic variants were identified in six probands, and a deep‐intronic variant was found together with an exon 20–22 deletion in one proband. Based on ophthalmologic findings and characteristics of the identified exonic variants present in trans, the deep‐intronic variants V1 and V4 were predicted to be relatively mild and severe, respectively. These findings are important for proper genetic counseling and for the development of variant‐specific therapies. A person with Stargardt disease (STGD1) carries a deletion of exons 20‐22 in one of two ABCA4 gene copies and a deep‐intronic mutation (c.5196+1137G>A) in the other copy. Both types of mutations cannot be identified using standard Sanger sequencing of the protein coding segments of the gene and require specific analyses. Deletions and deep‐intronic variants in ABCA4 can constitute up to 20% of ABCA4 mutations.